Local Service Delivery Problem: Social Services - YAPICIOĞLU, Esma; AKTEPE, Eray (Cankiri Karatekin Universitesi Iktisadi ve Idari Bilimler Fakultesi Dergisi, 2022)
The main purpose of the study is to determine whether the existence of more than one central and local public organization involved in the decision-making, administration and provision of social services is a complexity that negatively affects the effectiveness, efficiency and quality of the service, or a participatory management through coordination, cooperation and coordination. For this purpose, in the field research covering the city center and districts of Kastamonu province, data obtained by survey on planning, coordination and cooperation, human resources / personnel, budget and supervision for social work is analyzed proportionally within the framework of the descriptive (interpretive) analysis method within the qualitative research method. As a result of the research, it has been observed that unclear service delivery areas of the existing multi-actor structure in social service provision in Kastamonu causes repeat service, lack of service and to provide the easiest service. In the provision of social services provided in provinces that are not metropolitan cities, a coordination process to be established by the special provincial administration will ensure that the service can be provided more democratically, effectively and efficiently
Keywords: 11. Sustainability; 1. No poverty